Thực hiện phép tính 2. (x2 – 2xy +y2 )(x-2y) 3. (x+y+z)(x-y+z)4, 12a2b(a-b)(a+b) 5, (2×2-3x+5)(x2-8x+2) 26/07/2021 Bởi aihong Thực hiện phép tính 2. (x2 – 2xy +y2 )(x-2y) 3. (x+y+z)(x-y+z)4, 12a2b(a-b)(a+b) 5, (2×2-3x+5)(x2-8x+2)
2. (x2 – 2xy +y2 )(x-2y) = (2x – 2xy +2y)( x-2y) = 2x² – 2x²y +2xy -2xy + 2xy² + 4y² = 2x² – 2x²y +2xy² + 4y² + (2xy -2xy) = 2x² – 2x²y +2xy² + 4y² 3. (x+y+z)(x-y+z) = x² -xy + xz + xy – y² + yz + xz +yz +z² = x² -y² + z² + (xy-xy) + (xz+xz) + (yz + yz) = x² – y² + z² + 2xz + 2yz 4. 12a2b(a-b)(a+b) = 24ab(a-b)(a+b) = (24a²b – 24ab²)(a+b) = 24a³b + 24a²b² – 24a²b² – 24ab³ = 24a³b – 24ab³ 5. (2×2-3x+5)(x2-8x+2) = (4x – 3x +5)( 2x -8x +2) = 8x² – 32x² + 8x – 6x² + 24x² -6x +10x -40x +10 = (8x² -32x² – 6x² +24x²) + ( 8x – 6x +10x -40x ) +10 = -6x² 28x +10 CHÚC BẠN HỌC TỐT Bình luận
2. (x2 – 2xy +y2 )(x-2y)
= (2x – 2xy +2y)( x-2y)
= 2x² – 2x²y +2xy -2xy + 2xy² + 4y²
= 2x² – 2x²y +2xy² + 4y² + (2xy -2xy)
= 2x² – 2x²y +2xy² + 4y²
3. (x+y+z)(x-y+z)
= x² -xy + xz + xy – y² + yz + xz +yz +z²
= x² -y² + z² + (xy-xy) + (xz+xz) + (yz + yz)
= x² – y² + z² + 2xz + 2yz
4. 12a2b(a-b)(a+b)
= 24ab(a-b)(a+b)
= (24a²b – 24ab²)(a+b)
= 24a³b + 24a²b² – 24a²b² – 24ab³
= 24a³b – 24ab³
5. (2×2-3x+5)(x2-8x+2)
= (4x – 3x +5)( 2x -8x +2)
= 8x² – 32x² + 8x – 6x² + 24x² -6x +10x -40x +10
= (8x² -32x² – 6x² +24x²) + ( 8x – 6x +10x -40x ) +10
= -6x² 28x +10
CHÚC BẠN HỌC TỐT